Geomorphology, Shallow Subbottom Structure, and Sediments of the Atlantic Inner Continental Shelf off Long Island, New York. - Williams,S. Jeffress (1976)
About 800 square miles of the Atlantic Inner Continental Shelf off Long Island, New York,were studied by CERC to obtain information on the sea floor morphology, sediment distribution, and shallow subbottom stratigraphy and structure. This information is used for delineating sand and gravel resources and deciphering shelf geologic history. Basic survey data by CERC consist of 735 miles of high-resolution continuous seismic profiles and 70 vibratory cores; additional data were available from 82 sediment cores and 225 miles of seismic records. Data coverage extends from Atlantic Beach east to Montauk and in Gardiners Bay; and from the shoreface seaward about 10 miles to water depths of 105 feet. Numerous major buried ancestral drainage channels transect Long Island mainland in a north-south orientation and continue south across the shelf. Thalweg depths of the channels range from -100 to -550 feet MSL and channel widths are often several miles. Many channels on the north shore of Long Island underlie reentrant bays and most were significantly enlarged by Pleistocene glacial ice and later filled with sediment. Much of the surficial sand on the inner shelf is suitable as fill for beach restoration, except for that of the shoreface region (0 to-30 feet MSL) which contains fine sand and that of major parts of Gardiners Bay which contain organic-rich silt and clay. Topographic highs on the sea floor in the form of linear shoals, and broad deltalike platforms in eastern Long Island appear most suitable for sand recovery.